2017
DOI: 10.1016/j.chest.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does CAPTURE Translate?

Abstract: ClinicalTrials.gov; No.: NCT01880177; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Once again, further research is needed. Fourth, although CAPTURE has been tested and performs well identifying more severe, high-risk cases of COPD in Spanish-speaking patients, 2 sample size precluded testing its performance in milder symptomatic COPD. Finally, CAPTURE is a tool to identify patients requiring further evaluation for COPD; it was not intended to diagnose or evaluate treatment and may detect problems other than COPD that warrant evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, further research is needed. Fourth, although CAPTURE has been tested and performs well identifying more severe, high-risk cases of COPD in Spanish-speaking patients, 2 sample size precluded testing its performance in milder symptomatic COPD. Finally, CAPTURE is a tool to identify patients requiring further evaluation for COPD; it was not intended to diagnose or evaluate treatment and may detect problems other than COPD that warrant evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…COPD Assessment in Primary Care to Identify Undiagnosed Respiratory Disease and Exacerbation Risk (CAPTURE™) was developed to identify people with severe, high-risk undiagnosed COPD, defined as a forced expiratory volume in 1 second (FEV 1 ) <60% predicted or exacerbation risk, in primary care settings. 1 , 2 This case-finding method uses five simple patient-completed questions and the selective use of peak expiratory flow (PEF) to uncover individuals most likely to benefit from diagnosis and treatment. 1 8 The intent is to be as efficient as possible, using PEF selectively based on questionnaire score and reserving spirometry referrals to the subset of patients whose results warrant further diagnostic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“… 44–66 Only one studies recruited patients aged >18 years who were former or current smokers or symptomatic smokers, respectively. 61 The incidence of COPD is generally above 20% in studies that include people aged 40 or older with a smoking history and/or persistent symptoms. In contrast, studies that include people aged 18 and above have an incidence of COPD that is typically below 20%.…”
Section: Strategy For Copd Early Detection: Focus On Case-finding App...mentioning
confidence: 99%
“… 62 Quezada performed a study in Spain and demonstrated that the use of the combination of the CAPTURE questionnaire along with a PEF device yielded a higher AUC (0.953) than did the use of the CAPTURE questionnaire only (0.928). 61 The COLA questionnaire was developed by Siddharthan et al and used in combination with a PEF device for identifying individuals with COPD. The COLA questionnaire was used to evaluate respiratory symptoms, smoking or biomass exposure, and functional status.…”
Section: Strategy For Copd Early Detection: Focus On Case-finding App...mentioning
confidence: 99%